Identification and charactering of APX genes provide new insights in abiotic stresses response in Brassica napus - Jiao Pan; Lei Zhang; Min Chen; Yuxuan Ruan; Peifang Li; Zhihui Guo; Boyu Liu; Ying Ruan; Mu Xiao; Yong Huang (PeerJ, 2022)
Ascorbate peroxidase (APX) plays an important role in scavenging H2O2 and balancing ROS content in plant cells, which is of great significance for the growth and development of life and resistance to external stress. However, up to now, APXs in Brassica napus (B. napus) have not been systematically characterized. In this study, a total of 26 BnaAPX genes were identified, which were distributed on 13 chromosomes and divided into five phylogenetic branches. Gene structure analysis showed that they had a wide varied number of exons while BnaAPXs proteins contained more similar motifs in the same phylogenetic branches. qRT-PCR analysis of 26 BnaAPX gene expression patterns showed that three putative cytosol BnaAPX genes BnaAPX1, BnaAPX2, BnaAPX9, two putatice microsomal genes BnaAPX18 and BnaAPX25 were up-regulated rapidly and robustly under high salt, water shortage and high temperature stresses. In addition, the above three abiotic stresses led to a significant increase in APX activity. The results provide basic and comprehensive information for further functional characterization of APX gene family in B. napus.